Addressing behavioral impacts of childhood leukemia: A feasibility pilot randomized controlled trial of a group videoconferencing parenting intervention. (October 2016) - Williams, Lauren K.; McCarthy, Maria C.; Burke, Kylie; Anderson, Vicki; Rinehart, Nicole
Abstract: Purpose: Child emotional and behavioral problems constitute significant sequelae of acute lymphoblastic leukemia (ALL) treatment. The aims of this study were to a) examine the feasibility, acceptability and satisfaction of a parenting intervention amongst parents of children with ALL and b) explore whether participation in a parenting intervention shows promise for improvements in child behavior. Methods: 12 parents with a child aged between 2 and 8 years receiving maintenance phase treatment for ALL participated in a phase 2 randomized controlled trial comparing eight weeks of group online participation in Triple P: Positive Parenting Program with no intervention. Results: The number of eligible parents who completed the intervention was low (31.6%). Main reasons for non-consent or dropout were program time commitment too high or content not relevant. For parents who completed the intervention, satisfaction and acceptability was high. Parents reported the intervention as highly relevant and topical, feasible, helpful and a positive experience. Results indicated a non-significant trend towards improved total child behavioral and emotional difficulties following the intervention. Qualitative results indicated that intervention group parents reported improvements in parenting skills and competence, and decreased child behavioral problems. Conclusions: These pilot data highlight the difficulties of engaging and retaining parents in an 8-week parenting intervention in this context. For parents who completed the intervention, results indicated high feasibility, acceptability and satisfaction. Suggestions for further research and intervention modifications are provided to enhance uptake and strengthen efforts to assist parents in addressing child behavioral and emotional challenges during ALL treatment. Highlights: Engaging and retaining parents in an intervention in an oncology context is difficult. Parents completing study reported high levels of feasibility, acceptability, and satisfaction. With support, improvements in parenting skills and competence may be achieved.